Victor Vroom’s Expectation Theory: Application in Goat Smallholder Farmers in Indonesia - Guntoro, Budi (2016)
This research aimed to analyze the motivation of goat smallholder farmers joined the farmer group using Vroom’s Expectation Theory. Vroom’s expectancy theory differs from the content theories of Maslow, Alderfer, Herzberg, and McClelland in that Vroom’s expectancy theory does not provide specific suggestions on what motivates organization members. Instead, Vroom’s theory provides a process of cognitive variables that reflects individual differences in work motivation. The sample used in this study was goat farmers in Yogyakarta Provice. A total number of respodents was 162 farmers. Using the survey method, the result showed that farmers’ participation motivation category in the group housing was intermediate. The average value of valence was intermediate, expectancy was high, and instrumentality was intermediate. The average total score for motivation joining the group was intermediate. It can be concluded that farmers’ motivation joining group was in the intermediate category. The rank of the components underlying farmers’ motivation in group from the lowest to the highest was expectancy, instrumentality and valence